Association between diabetes and prevalence and growth rate of abdominal aortic aneurysms: A meta-analysis. (15th October 2016) - Xiong, Jiang; Wu, Zhongyin; Chen, Chen; Wei, Yingqi; Guo, Wei
Abstract: Background: Although the prevalence of abdominal aortic aneurysm (AAA) was lower in diabetes, the relationship between diabetes and AAA prevalence remains unclear. In this meta-analysis, we sought to clarify the effect of diabetes on prevalence and growth rate (GR) of AAA. Methods: We searched PubMed, Web of Science, Scopus and Cochrane databases. Articles reporting the AAA prevalence in diabetic patients and diabetic effects in GR of AAA were included. Results: Forty-nine studies on AAA prevalence in diabetics and thirteen studies on effect of diabetes in GR of AAA were included for meta-analysis. A strongly negative association was found between diabetes and AAA prevalence in population based screening (odds ratio [OR]adjusted : 0.66; 95% confidence interval [CI]: 0.58–0.75) and prospective studies (ORadjusted : 0.52; 95% CI: 0.43–0.63), but not in case–control studies (ORadjusted : 0.48; 95% CI: 0.20–1.15). Similar association was found in North American (ORadjusted : 0.62; 95% CI 0.54–0.71) and European (ORadjusted : 0.45; 95% CI 0.33–0.62) studies. The strongly negative association remained consistent after stratification by time of data collection (up to -1995 [ORadjusted : 0.65; 95% CI: 0.53–0.80], 1996–2005 [ORadjusted : 0.61; 95% CI: 0.47–0.78], 2006 and beyond- [ORadjusted : 0.67; 95% CI: 0.53–0.85], and data collection time > 10 years [ORadjusted : OR: 0.44; 95% CI 0.34–0.58]). The annual mean diabetic effect on AAA GR was − 0.60 mm/y (95% CI: − 0.76 — − 0.43). Conclusion: Diabetes was strongly and negatively associated with AAA prevalence regardless of study type, geography and time of data collection, as well as negative impact of diabetes on GR of AAA.